STUDY GUIDE EXAM 2: SOCL 222 - O’Brien, Jodi (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This exam will cover material from the readings in Part III and Part IV. It will be useful to ask yourself how the readings connect with the general logic of my essays and lectures.